Hydrocarbon degradation and separation of bilge water via a novel TiO2-HNTs/PVDF-based photocatalytic membrane reactor PMR) - Moslehyani, Ali (Royal Society of Chemistry, 2015)
This paper focuses on the potential of a novel flat sheet nanocomposite titanium dioxide (TiO2)-halloysite nanotubes (HNTs)/polyvinylidene fluoride (PVDF) membrane as a photocatalytic separator in the photocatalytic membrane reactor (PMR). The photocatalytic nanocomposite membrane acted the roles of both degradation and separation for bilge water. Both TiO2-HNTs photocatalyst and photocatalytic nanocomposite membranes were characterized by thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and field emission scanning electron microscopy (FESEM) combined energy dispersive X-ray spectroscopy (EDX). The hydrocarbon degradation and removal efficiency of the PMR was evaluated by gas chromatography mass spectroscopy (GC-MS). It was found that 99.9% of hydrocarbons were removed by the PMR within 8 h, which is likely due to uniform distribution and high effectiveness of the TiO2-HNTs photocatalyst in the PVDF polymer matrix. The TiO2 leaching from the nanocomposite membrane during the membrane permeation was analyzed using flame atomic adsorption spectrophotometer (AAS), which recorded 1.0 ppb of TiO2 leaching in the permeate tank